2015
DOI: 10.1093/humrep/dev136
|View full text |Cite
|
Sign up to set email alerts
|

Artificial oocyte activation to improve reproductive outcomes in women with previous fertilization failure: a systematic review and meta-analysis of RCTs

Abstract: PROSPERO CRD42014007445.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 56 publications
1
55
2
2
Order By: Relevance
“…Calcium signalling is crucial for oocyte activation and further embryonic development (Ducibella, Schultz, & Ozil, ; Kline & Kline, ; Marangos & Carroll, ; Ozil, Banrezes, Toth, Pan, & Schultz, ). An increase in fertilisation and cleavage‐stage embryo rates with the use of assisted oocyte activation protocols involving the use of Ca 2+ ‐ionophores has also been reported (Ebner et al., ; Heindryckx et al., ; Nikiforaki et al., ; Sfontouris et al., ; Vanden Meerschaut, Nikiforaki, Heindryckx, & De Sutter, ).…”
Section: Discussionmentioning
confidence: 86%
“…Calcium signalling is crucial for oocyte activation and further embryonic development (Ducibella, Schultz, & Ozil, ; Kline & Kline, ; Marangos & Carroll, ; Ozil, Banrezes, Toth, Pan, & Schultz, ). An increase in fertilisation and cleavage‐stage embryo rates with the use of assisted oocyte activation protocols involving the use of Ca 2+ ‐ionophores has also been reported (Ebner et al., ; Heindryckx et al., ; Nikiforaki et al., ; Sfontouris et al., ; Vanden Meerschaut, Nikiforaki, Heindryckx, & De Sutter, ).…”
Section: Discussionmentioning
confidence: 86%
“…The systematic review and meta-analysis of RCTs that compared ICSI-AOA and conventional ICSI first established that there is insufficient evidence available from RCTs to judge the efficacy and safety of ICSI-AOA for couples with previous fertilization failure [89]. A total of 14 articles were assessed and 9 included in meta-analysis.…”
Section: Success Rates Of Aoamentioning
confidence: 99%
“…Others have proposed electrical current-induced [4446] or specific mechanical manipulation approaches [47]. A recent meta-analysis of randomized controlled trials concluded that currently there is not sufficient data to support either methodology in cases of fertilization failure or “rescue ICSI” [48]. Obviously, none of these techniques present the physiological Ca 2+ oscillations.…”
Section: Alternative Sperm Factor Post-acrosomal Ww-domain Binding Prmentioning
confidence: 99%